Secrets beneath the soil: recovery of fern spores as a strategy of biodiversity conservation in Punta Lara Nature Reserve (PLNR), Argentina - Berrueta, Pedro Cayetano (2021)
The recovery of soil spores is a strategy to strengthen in decline or disappeared populations from natural environments. In this work, we analyzed 25 soil samples extracted from a patch of gallery forest in an “albardon” of Punta Lara Reserve, Buenos Aires. The samples were distributed in 50 Petri dishes, 25 exposed to controlled temperature and light and another 25 kept in darkness. To contribute to the identification of gametophytes and sporophytes, spores of the local species were cultured in vitro. In 18 months of trial, the appearance of gametophytes and sporophytes was observed, in a greater proportion those belonging to a dominant species in the community: Doryopteris concolor. Numerous gametophytes and sporophytes from Gastoniella chaerophylla were also obtained, a taxon not found in the “albardon” for two years. The germination index (GI) was estimated and the morphological characteristics of the gametophytes and sporophytes were recorded. This is the first contribution to the knowledge of the spore banks in Argentina, in a protected area where several threats put at risk the survival of native species. The bases to implement methods of ex situ and in situ conservation of native ferns are provided.